PENGARUH SOCIAL MEDIA MARKETING, BRAND IMAGE DAN BRAND TRUST TERHADAP MINAT BELI PRODUK WARDAH DI CIREBON - Dheana Nurfazlya; Sahara; Desty Cristya Anisa (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the impact of social media marketing, brand image, and brand trust on the purchase intention of Wardah products in Cirebon. In today's digital age, social media is a key platform for promoting products and building brand image, while brand trust plays a crucial role in establishing emotional connections with consumers. This quantitative research uses a survey approach to gather data from 97 respondents who have purchased Wardah products in Cirebon. The results indicate that brand image and brand trust have a positive and significant effect on purchase intention, while social media marketing does not have a significant influence. Nevertheless, the study provides insights into the importance of strengthening brand image and consumer trust to boost purchase intention, and suggests the need for improvements in social media marketing strategies to create a stronger impact on purchasing decisions.